2007
DOI: 10.1038/sj.onc.1210291
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function–rescue: the diverse nature of common p53 cancer mutants

Abstract: The tumor suppressor protein p53 is inactivated by mutation in about half of all human cancers. Most mutations are located in the DNA-binding domain of the protein. It is, therefore, important to understand the structure of p53 and how it responds to mutation, so as to predict the phenotypic response and cancer prognosis. In this review, we present recent structural and systematic functional data that elucidate the molecular basis of how p53 is inactivated by different types of cancer mutation. Intriguingly, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
419
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(431 citation statements)
references
References 121 publications
(177 reference statements)
9
419
0
3
Order By: Relevance
“…It has been shown that the zinc atom is important in stabilizing the DNA-binding domain structure of p53 (Cho et al, 1994) and for p53 DNA-binding activity in vitro and in vivo (Verhaegh et al, 1998). As a proof of principle, some p53 mutations in cancers (for example, mutation C242S, H179R, C176F and R175H) that perturb the zincbinding site in p53 result in the loss of DNA binding (Joenger and Fersht, 2007). Studies in vitro show that In the absence of HIPK2 (that binds p300 and stimulates p53/p300 corecruitment onto apoptotic target genes), Lys382 acetylation is inhibited and Ser46 phosphorylation alone is not sufficient to induce p53 apoptotic transcription.…”
Section: Role Of Hipk2 In Wt P53 Protein Conformationmentioning
confidence: 99%
“…It has been shown that the zinc atom is important in stabilizing the DNA-binding domain structure of p53 (Cho et al, 1994) and for p53 DNA-binding activity in vitro and in vivo (Verhaegh et al, 1998). As a proof of principle, some p53 mutations in cancers (for example, mutation C242S, H179R, C176F and R175H) that perturb the zincbinding site in p53 result in the loss of DNA binding (Joenger and Fersht, 2007). Studies in vitro show that In the absence of HIPK2 (that binds p300 and stimulates p53/p300 corecruitment onto apoptotic target genes), Lys382 acetylation is inhibited and Ser46 phosphorylation alone is not sufficient to induce p53 apoptotic transcription.…”
Section: Role Of Hipk2 In Wt P53 Protein Conformationmentioning
confidence: 99%
“…A majority of the mutations in p53 are located in the DNA-binding domain, with complex functional consequences. These mutations can affect the thermodynamic stability, folding rates of p53 and the interactions of p53 with DNA as well as with other partner proteins (Joerger and Fersht, 2007). Discovery of second site mutations that restore the activity of some of these mutants has provided clues for the restoration of activity by the use of small molecules.…”
Section: Targeting the P53 -Mdm2 Interactionmentioning
confidence: 99%
“…The disclosure of the structure of a co-crystal formed by the p53-DBD and a canonical p53 half-site revealed the principal features of the p53-DBD/DNA interface and formed the basis for understanding the structural premises underlying the loss of the sequence-specific transactivation function by mutp53 proteins (Cho et al, 1994). Since these seminal findings, the understanding of the biology of mutp53 proteins has advanced enormously, the quintessence being the realization that mutp53 proteins are extremely heterogeneous in their structural and possibly also in their biochemical properties (see Joerger and Fersht, 2007, this issue; reviewed by Sigal and Rotter, 2000). Underscoring the inequality of structural defects in the core domains of mutp53 proteins, the major activity of the core domain, SSDB, is impaired in individual mutp53 proteins to different degrees, with the severity of SSDB impairment spanning a broad range (see Joerger and Fersht, 2007;Menendez et al, 2007, this issue;Inga et al, 2001;Ang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since these seminal findings, the understanding of the biology of mutp53 proteins has advanced enormously, the quintessence being the realization that mutp53 proteins are extremely heterogeneous in their structural and possibly also in their biochemical properties (see Joerger and Fersht, 2007, this issue; reviewed by Sigal and Rotter, 2000). Underscoring the inequality of structural defects in the core domains of mutp53 proteins, the major activity of the core domain, SSDB, is impaired in individual mutp53 proteins to different degrees, with the severity of SSDB impairment spanning a broad range (see Joerger and Fersht, 2007;Menendez et al, 2007, this issue;Inga et al, 2001;Ang et al, 2006). However, except for the residual SSDB activity retained by the core domain of some mutp53 proteins, the principles of DNA recognition by mutp53 proteins and the role of mutp53 DNA binding for the oncogenic activities associated with some mutp53 proteins remains far from being clear.…”
Section: Introductionmentioning
confidence: 99%